Comparative Analysis Of Financial Stability In Enterprises Of Uzbekistan And Developed Countries: A Multi-Dimensional Approach (American Economist: Journal of Economics Finance and Global Policy, 2026)
Financial stability represents a fundamental pillar for sustainable enterprise development and macroeconomic resilience. This study provides a comparative analysis of financial stability in enterprises operating in Uzbekistan and developed economies. The findings indicate that enterprises in developed countries demonstrate stronger financial resilience due to diversified financial systems, advanced risk management frameworks, and deep capital markets. Conversely, enterprises in Uzbekistan remain highly dependent on bank financing. However, recent reforms have improved financial stability
Keywords: Financial Stability; Emerging Markets